2022
DOI: 10.3748/wjg.v28.i32.4574
|View full text |Cite
|
Sign up to set email alerts
|

Wumei pills attenuates 5-fluorouracil-induced intestinal mucositis through Toll-like receptor 4/myeloid differentiation factor 88/nuclear factor-κB pathway and microbiota regulation

Abstract: BACKGROUND Radiotherapy and chemotherapy can kill tumor cells and improve the survival rate of cancer patients. However, they can also damage normal cells and cause serious intestinal toxicity, leading to gastrointestinal mucositis[ 1 ]. Traditional Chinese medicine is effective in improving the side effects of chemotherapy. Wumei pills (WMP) was originally documented in the Treatise on Exogenous Febrile Diseases. It has a significant effect on chronic diarrhea and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…WMP is widely used in clinical practice, and numerous researchers have explored its mechanisms. [14,[20][21][22][23] However, there is currently a gap in research concerning the common mechanisms of action of WMP in treating both UC and T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WMP is widely used in clinical practice, and numerous researchers have explored its mechanisms. [14,[20][21][22][23] However, there is currently a gap in research concerning the common mechanisms of action of WMP in treating both UC and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that WMP alleviates UC symptoms by impacting inflammatory factors and the gut microbiota. [14] Furthermore, combined treatment with WMP and metformin for T2DM has resulted in significantly better outcomes compared to treatment with metformin alone. [15] These studies substantiate the concept of “treating different diseases with the same treatment.” However, there is limited research on the common mechanisms of WMP in treating both UC and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Quercetin has been shown to reduce the production of inflammatory factors through the NF-κB and MAPK pathways. [ 26 , 27 ] In addition, quercetin has a significant immunoregulatory effect, and it can inhibit the abnormal proliferation and activation of T lymphocytes and improve the chronic inflammation caused by the infiltration of T lymphocytes in the early stage of SS. [ 28 , 29 ] Kaempferol can regulate the Th1/Th2 cell subpopulation to achieve the goal of immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Naringenin, a natural product known for its antioxidative stress properties, inhibits macrophage M1 polarization by reducing the release of exosomal miR‐21‐3p derived from BEAS‐2B cells. 9 Schisandrol A, a bioactive constituent from Schisandrae Chinensis Fructus, has been reported to alleviate drug‐induced liver injury through autophagy activation via exosomes. 10 Shikonin, a naphthoquinone isolated from Lithospermum, inhibits human breast cancer cell proliferation by reducing tumor‐derived exosomes.…”
Section: Introductionmentioning
confidence: 99%